2018
DOI: 10.7175/fe.v19i1.1328
|View full text |Cite
|
Sign up to set email alerts
|

Albutrepenonacog alfa (Idelvion®) for the treatment of Italian patients with hemophilia B: a budget impact model

Abstract: BACKGROUND: Enhanced pharmacokinetic profile of albutrepenonacog alfa allows to prolong the interdose period in prophylaxis, maintaining higher trough level, and to reduce dosage needed for bleeding. This improvement could lead to a better efficiency of the hemophilia B treatment.OBJECTIVES: To estimate the impact of this new drug on the Italian National Health System (NHS).METHODS: A model was developed from the NHS perspective to assess the budget impact of treating severe hemophilia B with reimbursed recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The overall decrease in costs in the 3-year period was estimated to be −€1,988,068 ( Fig. 2 ), considering the weekly prophylactic dosages reported in the respective SPC for rFIX and data from clinical studies and the literature to estimate the number of bleeding episodes and management ( 12 , 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 34 , 36 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall decrease in costs in the 3-year period was estimated to be −€1,988,068 ( Fig. 2 ), considering the weekly prophylactic dosages reported in the respective SPC for rFIX and data from clinical studies and the literature to estimate the number of bleeding episodes and management ( 12 , 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 34 , 36 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…b) Nonacog gamma: to estimate the amount of drug used in children <12 years of age, bleeding rates were taken from the EPAR (36), and rFIX dose was considered to be the same as administered in adults (12). c) Nonacog alfa: mean dose used for prophylaxis was applied to management of bleeding episodes, multiplied by the mean number of infusions needed to treat a bleeding episode (34).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adult patients who require a high number of infusions or those poorly controlled with the former treatment can also especially benefit from rIX-FP, since the reduction in the number of injections can entail an even larger increase in quality of life, and it could be a cost-effective option. Actually, a recent pharmacoeconomic model assessed the budget impact of treating severe hemophilia B with reimbursed rIX-FP over 3 years in Italy, concluding that rIX-FP is expected to decrease pharmaceutical costs [50]. A recent real world study found that the cost per success (defined as patients experiencing no spontaneous bleeding) in patients switching from nonacog alfa to rIX-FP was reduced by 29% in Italy, 55% in Belgium, and 50% in the United Kingdom.…”
Section: Expert Opinionmentioning
confidence: 99%